DEVELOPING A MULTI-HOP BLE NETWORK TO MONITOR PATIENTS WITH CHRONIC DISEASES - KHAN, AURANGZAIB (2017)
Bluetooth LE, which is also known as Bluetooth Smart in the market, was introduced to the world as an enhanced and a better alternative than Bluetooth Classic. Bluetooth Classic has become an obsolete technology as compared to the Bluetooth LE, in terms of the bandwidth it covers and the power it consumers to run. The frequency wireless hopping technology used by Bluetooth LE in the 2.4 GHz unlicensed radio band is a commendable technology used to interconnect nearby devices, and far better than the classic Bluetooth.